Liberating Oppressed Class, Community and Gender:Some Reflections - Tuladhar, Subarna Man (Administration and Management Review, 2009)
All indicators continue to show a greatly disadvantaged position of theoppressed class, community and gender in the Nepalese society. Manysocial activists believe that institutionalized discrimination between menand women, among men and men can be removed gradually throughegalitarian laws and social practices. The present article, however,seems to contend that the oppressed people's perception of themselveshas a key role to play in their empowerment for eliminating suchdiscrimination in and outside their families to effect contemplatedchange in the society.Administration and Management Review Vol. 21, No. 1, January, 2009, Page 46-57